Synthesis of bio-polymer based composite binder for utilization of industrial coke dust waste. (1st March 2022) - Kumar Patra, Sovan; Ghorai, Soumitra; Sahu, Nilamadhaba; Kapure, Gajanan U.; Kumar Tripathy, Sunil
Graphical abstract: Highlights: A novel organic binder starch grafted acrylamide with bentonite dispersed is synthesized. Excellent grafting efficiency with enhanced bonding performance for composite binder. The binder has a good thermal stability and cold crushing strength. Briquette formed have excellent water resistance index along with binding properties. Abstract: In the present investigation, a novel composite binder which aids in forming coke briquettes from industrial waste coke dust were synthesized in one pot setup. The composite binder enables efficient utilization of the coke fines by their reformulation into coke briquettes. The novel binder has been characterized by scanning electron microscopy, Fourier transform infrared spectrophotometry, X-ray diffraction, X-ray photonic spectroscopy and nuclear magnetic resonance spectrometry to understand the grafting efficiency and bentonite as filler incorporation. The composite binder with a secondary filler (bentonite) and a secondary binder (ordinary Portland cement) was mixed in definite proportion to obtain the compound binder. The coke briquette was made from coke fines and compound binder in a fixed ratio confers to high thermal stability with improved cold compressive strength. The high-temperature study indicates that the characteristics of coke briquette resemble that of coke used in submerged arc furnaces for ferroalloy production.